Spinal Epidural Hematoma Caused by Pseudogout: A Case Report and Literature Review. (June 2014) - deSouza, R. M.; Uff, C.; Galloway, M.; Dorward, N. L.
Study Design: Case report. Objective: We present the first reported case of spontaneous spinal epidural hematoma secondary to calcium pyrophosphate crystal deposition disease (pseudogout) in a 75-year-old woman. Methods: A retrospective review of the patient's case notes was undertaken and the limited literature on this subject reviewed. Results: This patient presented with sudden-onset lower limb paresis, sensory loss, urinary retention, and back pain. Magnetic resonance imaging showed an epidural hematoma, which was evacuated. Histologic specimens of the clot showed calcium pyrophosphate dihydrate crystal deposits (pseudogout). Conclusion: The importance of histopathologic review of surgical specimens is highlighted when considering the differential diagnosis of apparently spontaneous spinal epidural hematoma.